Role of tunable polymer flexibility in controlling wetting behavior and thermal properties of poly(1, 3‐cyclohexadiene)‐silica nanocomposites. (19th November 2021) - Bornani, Kamlesh; Shah, Priyank; Barkakaty, Balaka; Chen, Jihua; Lokitz, Bradley; Mays, Jimmy; Kilbey, S. Michael
Abstract: We present how altering the chain flexibility affects the nanoscale organization of polymer‐grafted nanoparticles (PGNPs) and its ultimate impact on macroscale thermal properties. To isolate the role of chain flexibility on wetting behavior in athermal polymer nanocomposites (PNC), the graft and matrix chemistry is kept identical by utilizing 1, 3‐cyclohexadiene‐based polymer materials. Increasing the rigidity and molecular weight of both the graft and matrix is found to favor mixing of poly(1, 3‐cyclohexadiene) PCHD‐grafted silica NPs with the matrix, supported by a concomitant increase in glass transition temperatures of the PNCs. Further, the associated entropic factors that drive wetting behavior and dispersion of PGNPs are discussed, emphasizing the dominant role‐played by chain flexibility. Alterations in graft flexibility had the strongest impact on dispersion and T g values of the PNC, while molecular weight (MW) plays a secondary role. This investigation is a unique demonstration of how chain flexibility alteration in athermal semiflexible systems can be used to alter NP organization by altering filler‐matrix wettability which also impacts thermal properties. Abstract : Increasing the 1, 2 linkages in the PCHD backbone increases the rigidity of the chain. The resultant decrease in chain conformational entropy is accompanied by improved mixing, suggesting that the system entropy increases. Using polymer‐grafted nanoparticles, it is shown that mixing is enhanced when rigidity of graft and matrix chains are increased, with the impact of graft rigidity being more dominant.